Route Network Optimization in the Dakar Airspace: Surface Navigation - Emani, Mint Elhassen; Coulibaly, Amadou; Diagne, Salimata G.; Haouba, Ahmedou Ould; Mby, Alain Ngoma (Current Overview on Science and Technology Research Vol. 1, 2022)
In this study, the map of a network of air routes was upgraded by deleting the non-optimal routes and substituting the best ones. A linear programming model for integers was created. The goal was to find optimal routes in superspace using performance-based navigation. The shortest path in a graph is determined via the DIJKSTRA method, which is how the best routes were discovered. The benefits of surface navigation were demonstrated in simulations using the Python programming language in locations with heavy traffic. The conceptual stage and the higher airspace were investigated in this work.